2017
DOI: 10.1002/ptr.5826
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Benefit and Tolerability of IQP‐CL‐101 (Xanthofen) in the Symptomatic Improvement of Irritable Bowel Syndrome: A Double‐Blinded, Randomised, Placebo‐Controlled Clinical Trial

Abstract: Irritable bowel syndrome (IBS) is a functional bowel disorder of unknown aetiology. There is currently no known cure, and pharmacological interventions are usually targeting symptomatic relief, where natural and herbal remedies also play a role. This study aimed to evaluate the benefit and tolerability of IQP‐CL‐101 in symptomatic IBS relief. A double‐blinded, randomised, placebo‐controlled trial was conducted over 8 weeks. A total of 99 subjects fulfilling ROME‐III criteria for IBS were randomised into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Good‐quality clinical trials represent the key research tool for advancing medical knowledge and patient care (Figure ). For example, the double‐blind, randomised, placebo‐controlled trial reported by Alt et al fulfils the quality criteria for clinical trials and allows conclusions to be drawn from a good level of EBM (Alt, Chong, Teng, & Uebelhack, ). In this study, the authors correctly randomised the participants, and inclusion/exclusion criteria were clearly defined.…”
Section: Interpreting and Translating Evidence‐based Phytotherapy Intmentioning
confidence: 99%
See 1 more Smart Citation
“…Good‐quality clinical trials represent the key research tool for advancing medical knowledge and patient care (Figure ). For example, the double‐blind, randomised, placebo‐controlled trial reported by Alt et al fulfils the quality criteria for clinical trials and allows conclusions to be drawn from a good level of EBM (Alt, Chong, Teng, & Uebelhack, ). In this study, the authors correctly randomised the participants, and inclusion/exclusion criteria were clearly defined.…”
Section: Interpreting and Translating Evidence‐based Phytotherapy Intmentioning
confidence: 99%
“…on irritable bowel syndrome. The results showed significant reduction in severity of symptoms, with consequent improvement in patient quality of life (Alt et al, ). This high‐quality study clearly contributes to our understanding of whether an analysed phytotherapy can be an effective treatment strategy.…”
Section: Interpreting and Translating Evidence‐based Phytotherapy Intmentioning
confidence: 99%
“…With regard to the possible side effects of curcumin use, human trials assessing its safety and toxicity have found it to be safe, with occasional reports of slight giddiness, nausea, and diarrhoea [ 42 ]. Encouragingly, no adverse events were also reported in any of the trials reviewed in this study [ 24 , 25 , 26 , 28 ]. However, at higher doses, curcumin may interact with some medications, such as anticoagulants [ 43 ].…”
Section: Discussionmentioning
confidence: 83%
“…Overall, random-effects meta-analysis based on three studies and 326 subjects found curcumin to have beneficial but not statistically significant effects on IBS symptoms. Of the five clinical trials reviewed, three reported positive and significant effects for curcumin-containing products [ 24 , 26 , 28 ], while two [ 25 , 27 ] found no significant effects compared to placebo and advised against monotherapy with curcumin. It is important to note that in the study by Brinkhaus et al [ 25 ], diagnosis of IBS was not based on the established Rome Criteria [ 29 ], but rather an intensive clinical examination ruling out other organic causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation